Recognition of and response to neonatal intrapartum-related complications in home-birth settings in Bangladesh - Vanderende, Kristin E; Moran, Allisyn C; Leasure, Karen; Day, Louise T; Afsana, Kaosar; Kalim, Nahid; Munira, Shirajum; Rahman, Nazneen; Islam, Munia; Khan, Jasmin; Sibley, Lynn (© 2014 International Centre For Diarrhoeal, Disease Research, Bangladesh, 2017)
This article was published in the Journal of Health, Population and Nutrition [© 2014 International Centre For Diarrhoeal, Disease Research, Bangladesh] and The Journal's website is at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4221456/